Population dynamics of Megalaspis cordyla (Linnaeus, 1758) from northeastern part of the Bay of Bengal, Bangladesh - Zafar, Mohammad; Mustafa, M G; Haque, M Anna (Indian Journal of Fisheries, 2011)
Population parameters of Megalaspis cordyla from the trawl catches in the northeastern part of the Bay of Bengal were estimated based on length-frequency data. The asymptotic length (LÂ°Â°) and growth constant (K) were estimated as 37.90 cm (total length) and 0.58/year respectively. The total mortality co-efficient (Z) was 1.75. The estimated natural mortality (M) was 1.17 and the fishing mortality co-efficient (F) was 0.58. The estimated value for the exploitation rate (E) using the length converted catch curve was 0.33. The recruitment was continuous with two peaks per year. The sizes of M. cordyla at 25, 50 and 75 per cent probabilities of capture were 20.26, 21.80 and 23.34 cm respectively. The length-weight relationship for combined sex was W=0.01794 TL2818.